Structure‐Activity Relationship of NF023 Derivatives Binding to XIAP‐BIR1 - Sorrentino, Luca (ChemistryOpen, 2019)
Inhibitors of Apoptosis Proteins (IAPs) are conserved E3‐ligases that ubiquitylate substrates to prevent apoptosis and activate the NF‐kB survival pathway, often deregulated in cancer. IAPs‐mediated regulation of NF‐kB signaling is based on the formation of protein complexes by their type‐I BIR domains. The XIAP‐BIR1 domain dimerizes to bind two TAB1 monomers, leading to downstream NF‐kB activation. Thus, impairment of XIAP‐BIR1 dimerization could represent a novel strategy to hamper cell survival in cancer. To this aim, we previously reported NF023 as a potential inhibitor of XIAP‐BIR1 dimerization. Here we present a thorough analysis of NF023 binding to XIAP‐BIR1 through biochemical, biophysical and structural data. The results obtained indicate that XIAP‐BIR1 dimerization interface is involved in NF023 binding, and that NF023 overall symmetry and the chemical features of its central moiety are essential for an efficient interaction with the protein. Such strategy provides original hints for the development of novel BIR1‐specific compounds as pro‐apoptotic agents.